The Occupational Risk of Influenza A (H1N1) Infection among Healthcare Personnel during the 2009 Pandemic: A Systematic Review and Meta-Analysis of Observational Studies. - Janna Lietz; Claudia Westermann; Albert Nienhaus; Anja Schablon (PLoS ONE)
Introduction The aim of this review was to record systematically and assess the published literature relating to the occupational risk of influenza A (H1N1) infection among healthcare personnel during the 2009 pandemic. Methods The literature search was performed in June 2015. An update was carried out in May 2016. It was applied to the electronic databases EMBASE, MEDLINE, PsycINFO, PubMed, CINAHL and Google Scholar. The quality assessment was conducted with a tool using eight criteria. A meta-analysis was carried out to compute pooled effect estimates for influenza A (H1N1) infection. Results A total of 26 studies were included in the review, 15 studies met the criteria for the meta-analysis. After a sensitivity analysis the pooled analysis showed a significantly increased odds for influenza A (H1N1) infection for healthcare personnel compared to controls/comparisons (OR = 2.08, 95% CI = 1.73 to 2.51). The pooled prevalence rate for healthcare personnel alone was 6.3%. Conclusions This review corroborates the assumption that healthcare personnel were particularly at risk of influenza A (H1N1) infection during the 2009 pandemic. Healthcare facilities should intensify their focus on strategies to prevent infections among healthcare personnel, especially during the first period of pandemics.